Cover Feature: Discovery and Evaluation of New Activity‐Based Probes for Serine Hydrolases (ChemBioChem 17/2019). (21st August 2019) - Wang, Chao; Abegg, Daniel; Dwyer, Brendan G.; Adibekian, Alexander
Abstract : The cover feature picture shows one of our new phenoxy phosphonate probes in the active site of prolyl oligopeptidase (PREP), a serine hydrolase implicated in many neurological diseases and a target of the probe as revealed by LC‐MS/MS‐based proteomics. The new activity‐based serine hydrolase probes offer many advantages over commercial fluorophosphonate probes including ease of preparation, excellent cell permeability, and distinct reactivity profiles. The image of the PREP active site was produced from PDB ID: 3DDU by using Maestro (Schrödinger). More information can be found in the communication by A. Adibekian et al. onpage 2212 in Issue 17, 2019 (DOI:10.1002/cbic.201900126 ).